Design and Development of Coal Mining Equipment Inspection Instrument Application System - Chenguang Zhao (Sensors & Transducers, 2014)
Based on the inspection instrument, the paper has offered an equipment inspection instrument regular repairing application system suited to the characteristics of coal enterprises. This system works stably in coal enterprises, effectively completing the measurement and management of equipment inspection, improving the reliability of the equipment, reducing the incidence of failure.